Simulating and stimulating performance: developing a next-generation music performance simulator - Waddell, George; Bland, Richard; Williamon, Aaron (Frontiers in Psychology, 2025)
The spaces where musicians practice often differ considerably from where they perform. As such, musicians are an emblematic example of performers who must adapt their skillset to contexts where the visual, aural, social, and psychological environment introduces significant increases in variety, risk, and pressure. Numerous domains address this disparity through the use of simulation, giving the performer the opportunity to learn and challenge their skills in contexts more closely resembling real-world conditions. This article describes the implementation of simulation in music performance contexts through the development of the second generation of performance simulation technologies at the Royal College of Music. It outlines the design requirements for a large, immersive space with a high degree of flexibility in recreating the visual and acoustic atmosphere of a performance stage and corresponding backstage area, while also facilitating performance capture and analysis. Applications for such a facility are outlined to advance research, teaching, and knowledge exchange within and beyond music performance.